Kedudukan Fudisia Sebagai Jaminan Pemberian Kredit - Muh Rusli; Patahillah Asba; Lia Trizza Firgita Adhilia (Jurnal Litigasi Amsir, 2023)
This research was conducted with the aim of knowing the procedure for granting credit with a fiduciary guarantee at PT BPR Hasamitra Sidenreng Rappang. And to find out the rights and obligations of the giver and recipient of a fiduciary guarantee in the event of a credit default at PT BPR Hasamitra Sidenreng Rappang. The type of research in this study is normative and empirical, which in other words is a type of sociological legal research and can also be called field research. The results of the study show that in the implementation of providing credit with fiduciary guarantees to customers, PT BPR Hasamitra Sidenreng Rappang has stages or procedures that must be carried out first. The difference is in granting credit with a fiduciary guarantee, after going through the stages of the procedure for granting a fiduciary guarantee, then a Fiduciary Deed must be drawn up at a notary to provide legal certainty and then registered with the Fiduciary Registration Office to provide legal certainty and give priority to creditors who register collateral. the fiduciary to the Fiduciary Registration Office. And creditors (fiduciary recipients) or PT BPR Hasamitra Sidenreng Rappang and Debtors (fiduciary givers) have their respective rights and obligations that must be fulfilled and implemented. Especially if the debtor defaults and is at risk, if the default can be carried out by auction or underhand sales, whereas if there is a risk of damage or loss of goods, then they are replaced with collateral that is the same value as the previous collateral.